T cell-specific constitutive active SHP2 enhances T cell memory formation and reduces T cell activation - Cammann, Clemens; Israel, Nicole; Frentzel, Sarah; Jeron, Andreas; Topfstedt, Eylin; Schüler, Thomas; Simeoni, Luca; Zenker, Martin; Fehling, Hans Joerg; Schraven, Burkhart; Bruder, Dunja; Seifert, Ulrike (Frontiers in Immunology, 2022)
Upon antigen recognition by the T cell receptor (TCR), a complex signaling network orchestrated by protein-tyrosine kinases (PTKs) and protein-tyrosine phosphatases (PTPs) regulates the transmission of the extracellular signal to the nucleus. The role of the PTPs Src-homology 2 (SH2) domain-containing phosphatase 1 (SHP1, Ptpn6) and Src-homology 2 (SH2) domain-containing phosphatase 2 (SHP2, Ptpn11) have been studied in various cell types including T cells. Whereas SHP1 acts as an essential negative regulator of the proximal steps in T cell signalling, the role of SHP2 in T cell activation is still a matter of debate. Here, we analyzed the role of the constitutively active SHP2-D61Y-mutant in T cell activation using knock-in mice expressing the mutant form Ptpn11D61Y in T cells. We observed reduced numbers of CD8+ and increased numbers of CD4+ T cells in the bone marrow and spleen of young and aged SHP2-D61Y-mutant mice as well as in Influenza A Virus (IAV)-infected mice compared to controls. In addition, we found elevated frequencies of effector memory CD8+ T cells and an upregulation of the programmed cell death protein 1 (PD-1)-receptor on both CD4+ and CD8+ T cells. Functional analysis of SHP2-D61Y-mutated T cells revealed an induction of late apoptosis/necrosis, a reduced proliferation and altered signaling upon TCR stimulation. However, the ability of D61Y-mutant mice to clear viral infection was not affected. In conclusion, our data indicate an important regulatory role of SHP2 in T cell function, where the effect is determined by the kinetics of SHP2 phosphatase activity and differs in the presence of the permanently active and the temporally regulated phosphatase. Due to interaction of SHP2 with the PD-1-receptor targeting the protein-tyrosine phosphatase might be a valuable tool to enhance T cell activities in immunotherapy.